In Vitro Antibacterial Activity of Crude Extracts of Artocarpus heterophyllus Seeds against Selected Diarrhoea-Causing Superbug Bacteria - Asio Eve; Adamu Almustapha Aliero; Doreen Nalubiri; Rasheed Omotayo Adeyemo; Saheed Adekunle Akinola; Theophilus Pius; Saphurah Nabaasa; Susan Nabukeera; Bashir Alkali; Ibrahim Ntulume (The Scientific World Journal)
The current upsurge in resistance to conventional antibiotics, as well as high cost of orthodox medical treatment, called for the use of medicinal plants as an alternative therapy. This research was aimed at determining the antibacterial activity of Artocarpus heterophyllus seed extracts (Jackfruit as it is locally called) in the treatment of diarrhoea. Ethanolic and hexanolic seed crude extracts of the plant were screened for antidiarrhoeal activity against bacteria isolated from clinical samples (methicillin-resistant and susceptible Staphylococcus aureus, multidrug-resistant Pseudomonas aeruginosa, ciprofloxacin-resistant Salmonella typhimurium, and third-generation cephalosporin-resistant Escherichia coli). Plant phytochemical screening was conducted using standard methods. The antibacterial activity was carried out using the agar well diffusion method and compared to the standard antibiotics ceftriaxone and vancomycin. The minimum inhibitory concentration was determined by the microbroth dilution method, whereas the minimum bactericidal concentration was determined by plating out from microtitre plates with no visible growth. The results of phytochemical screening revealed the presence of tannins, flavonoids, reducing sugars, cardiac glycosides, saponins, and steroids from the prepared crude extracts. The ethanolic and hexanolic extracts had activity on multidrug-resistant Pseudomonas aeruginosa, methicillin-resistant Staphylococcus aureus, and methicillin-susceptible Staphylococcus aureus with the mean and standard error zone of inhibition that ranged from 8.5 ± 0.5 to 16.5 ± 0.25 mm; however, the extracts were found not to have activity on resistant E. coli and Salmonella typhimurium. The ethanolic crude extract had the lowest MIC and MBC values of 31.25 and 125 mg/ml, respectively, compared to the hexane extract which had the MIC and MBC values of 62.50 and 250 mg/ml, respectively. This provides the evidence for its usage as an alternative herbal remedy for the treatment of diarrhoea caused by susceptible and methicillin-resistant Staphylococcus aureus and multidrug resistant Pseudomonas aeruginosa.